The Implementation of Discovery Learning Models in Enhancing Speech Script Writing Skills for Students - Sarimanah, Eri; Dewi, Figiati Indra; Efendi, Roy; Suhendra, Suhendra; Nurul, Muhamad; Soeharto, Soeharto (Bina Nusantara University, 2019)
This research investigated the use of discovery learning models to enhance students’ speech script writing skills. This research aimed to focus on the study of the effectiveness and difficulties of discovery learning models to improve students’ speech script writing skills. The research applied an experimental method by using test, observation, and questionnaires for collecting data techniques. The population of this research was students of MTs Syarikal Islam 2 Kalapanunggal. The class of IX-B was the experimental class, and a class of IX-A was control class. The use of the discovery learning model is proven to enhance students’ speech script writing skills. The effectiveness of this experimental model is shown that the average score of the pretest of the experimental class is 53,5, and the post-test score is 84,3. By comparing the control class without treatment, it indicates the effectiveness of the intervention in the experimental class. The research shows a meaningful comparison of the experimental class and control class, which gain 2,56 by using the t-test. The data obtains that t-count is higher than t-table or significant is the value of t-table<t-count, namely 1,68 < 2,56 > 2,42. Therefore, it can be concluded that the discovery learning model has shown the improvement for students’ speech script writing skills effectively.